The Chaldean Account of Genesis. Containing the Description of the Creation, the Fall of Man, the Deluge, the Tower of Babel, the Time of the Patriarchs, and Nimrod; Babylonian Fables, and Legends of the Gods; from the Cuneiform Inscriptions - Smith, George (1977)
Reprint; 4875